Related of the Age, Body Mass Index and Anti-Müllerian Hormone with the Other Hormones in Polycystic Ovarian Syndrome Patients - Al-Ardi, Musafer (MultiTech Publisher, 2023)
Hormonal disorders affecting ageing and hormone levels significantly impact polycystic ovary syndrome (PCOS), which is linked to infertility. PCOS and obesity have a two-way overlap, affecting hormone concentrations with weight and age in PCOS-affected women. The study measured hormone concentrations in the blood serum of 62 POCS patients and found that BMI-related variables were negative with E2, insignificant negative association with HCG E2, Inhibin B, TSH, and FSH, insignificant positive association with prolactin LH, and age. Age-related variables were negative with AMH, HCG_E2, and prolactin, or positive with BMI, Inhibin, FSH, LH, and TSH, but insignificant. AMH changed positively with HCG E2, inhibin B, prolactin, and LH, and negatively with rest hormones. BMI is positively affected by a woman's age and PCOS, and age affects the production of inhibin, FSH, LH, and TSH. Therefore, the relationship between AMH and age is negative.